Transformational Leadership Impact and Compentation toward Implementation of Work Motivation on XYZ Vocational School Teacher Performance - Fridayanti, Fina; Ditosumarto, Ngadino Surip; Edi, Satrio Wibowo (International Humanities and Applied Science Journal, 2019)
The This study aims to discuss about transformational leadership impact and compensation toward implementation of work motivation on XYZ Vocational School teacher performance. This object are XYZ Vocational School teacher of 60 respondents that have different work experience and educational background. This study used SEM data analysis techniques and used Smart PLS 3.2.7. Versions. The population used all XYZ Vocational School teachers of 60 respondents. The results of data examination and calculation, is acquired the output from the positive and significant impact of leadership toward teacher motivation and performance, and a motivation as endegenous variable that makes positive and significant impact on teacher performance. Exogenous variables (transformational leadership and compensation) toward motivation that is acquired by result R-square (R2) = 0.760. Then exogenous variables (transformational leadership and compensation) toward work performance teacher that is acquired by result R-square (R2) = 0.839. Base on this explains that determination of exogenous variable (transformational leadership and compensation) on endogenous variable (motivation and work performance) are moderately high.